Pelatihan Budidaya Tanaman Organik dan Pengolahan Makanan Sehat pada Guru Raudhatul Athfal Sukorejo - Mamilianti, Wenny (Universitas Muhammadiyah Malang, 2025)
Purpose – The aim of this activity is to improve the knowledge and skills of Raudhatul Athfal teachers in cultivating organic plants and processing healthy food as an effort to encourage students to enjoy eating vegetables and fish. Design/methodology/approach – The method of implementing community service is to use a training approach, activity evaluation and mentoring. The training activities were carried out on July 31, 2024 and August 10, 2024 in the meeting room and yard of IGRA Sukorejo. The training activity was then continued with mentoring activities and an evaluation of the training. The results of the activity evaluation are used for technical recommendations for mentoring target partners. Findings – The result of this community service activity is that teachers of Raudhatul Athfal Sukorejo gain knowledge and information about organic plant cultivation and healthy food processing with raw materials available around their homes. The evaluation results show an increase in the knowledge and skills of teachers in plant cultivation and healthy food processing. This is indicated by the presence of target partners who have started to apply technology and have succeeded in making healthy food at their workplace and at home. Originality/value – This community service activity provides environmentally friendly and safe organic plant cultivation technology for early childhood, in addition to food processing using raw materials that are usually grown at home or in Raudhatul Athfal educational units. The technology provided becomes material in the Raudhatul Athfal (RA) or PAUD Learning Implementation Plan.